Identification and characterisation of Simiate, a novel protein linked to the fragile X syndrome. - Kristin Derlig (Public Library of Science (PLoS), 2013)
A strict regulation of protein expression during developmental stages and in response to environmental signals is essential to every cell and organism. Recent research has shown that the mammalian brain is particularly sensitive to alterations in expression patterns of specific proteins and cognitive deficits as well as autistic behaviours have been linked to dysregulated protein expression. An intellectual disability characterised by changes in the expression of a variety of proteins is the fragile X syndrome. Due to the loss of a single mRNA binding protein, the Fragile X Mental Retardation Protein FMRP, vast misregulation of the mRNA metabolism is taking place in the disease. Here, we present the identification and characterisation of a novel protein named Simiate, whose mRNA contains several FMRP recognition motifs and associates with FMRP upon co-precipitation. Sequence analysis revealed that the protein evolved app. 1.7 billion years ago when eukaryotes developed. Applying antibodies generated against Simiate, the protein is detected in a variety of tissues, including the mammalian brain. On the subcellular level, Simiate localises to somata and nuclear speckles. We show that Simiate and nuclear speckles experience specific alterations in FMR1(-/-) mice. An antibody-based block of endogenous Simiate revealed that the protein is essential for cell survival. These findings suggest not only an important role for Simiate in gene transcription and/or RNA splicing, but also provide evidence for a function of nuclear speckles in the fragile X syndrome. Indeed, transcription and splicing are two fundamental mechanisms to control protein expression, that underlie not only synaptic plasticity and memory formation, but are also affected in several diseases associated with mental disabilities.